Constitutional Control of Legislative Abstinence - Comparative Analytical Study - األستاذ المساعد الدكتور عبدالفتاح عبدالرزاق محمود; المدرس المساعد محمد عبدالكريم شريف (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Control over the constitutionality of laws is one of the means necessary to ensure the proper operation of the constitutional rules. In order to achieve this goal, most of the comparative constitutions of the judiciary determine the right to consider the constitutionality of the legislation issued and to decide whether or not to reconcile them, additionally, some constitutions give power to the constitutional judiciary to monitor the non-enactment of legislation in the constitution which stipulated the need to issue them. This study discusses the concept of control over the constitutionality of legislative abstention by analyzing the constitutional texts regulating this subject, and comparing the Iraqi constitutional system with the comparative constitutional systems that have been addressed this issue. The constitutions in dealing with this important issue did not adopt a single trend, some of which explicitly stated the idea of legislative abstention, and from which silent. However, in the 2005 Iraqi Constitution, there is little provision on the judicial control of legislative abstention. Therefore, is it permissible for the judiciary to impose control over the constitutionality of the legislative omission?, in other words, does the judiciary can exercise jurisdiction that is not exclusively contained in the constitution?. In our view, the problem does not lie in the fact that there is no provision for exercising of this jurisdiction insofar as it lies in the hesitancy of the Federal Supreme Court to judge and adjudicate in what is not found in the text of the Constitution or the law.